Targeting DNA Replication and Repair for the Development of Novel Therapeutics against Tuberculosis - Reiche, Michael A.; Warner, Digby F.; Mizrahi, Valerie (Frontiers in Molecular Biosciences, 2017)
Mycobacterium tuberculosis is the etiological agent of tuberculosis (TB), an infectious disease which results in approximately 10 million incident cases and 1.4 million deaths globally each year, making it the leading cause of mortality from infection. An effective frontline combination chemotherapy exists for TB; however, this regimen requires the administration of four drugs in a two month intensive phase followed by a continuation phase of a further two months with two of the original drugs, and is only effective for the treatment of drug-sensitive TB. The emergence and global spread of multidrug-resistant (MDR) and extensively drug-resistant (XDR) strains of M. tuberculosis and the complications posed by co-infection with the human immunodeficiency virus (HIV) and other co-morbidities such as diabetes have prompted urgent efforts to develop shorter regimens comprising new compounds with novel mechanisms of action. This demands that researchers re-visit cellular pathways and functions that are essential to M. tuberculosis survival and replication in the host but which are inadequately represented amongst the targets of current anti-mycobacterial agents. Here, we consider the DNA replication and repair machinery as a source of new targets for anti-TB drug development. Like most bacteria, M. tuberculosis encodes a complex array of proteins which ensure faithful and accurate replication and repair of the chromosomal DNA. Many of these are essential; so, too, are enzymes in the ancillary pathways of nucleotide biosynthesis, salvage, and re-cycling, suggesting the potential to inhibit replication and repair functions at multiple stages. To this end, we provide an update on the state of chemotherapeutic inhibition of DNA synthesis and related pathways in M. tuberculosis. Given the established links between genotoxicity and mutagenesis, we also consider the potential implications of targeting DNA metabolic pathways implicated in the development of drug resistance in M. tuberculosis, an organism which is unusual in relying exclusively on de novo mutations and chromosomal rearrangements for evolution, including the acquisition of drug resistance. In that context, we conclude by discussing the feasibility of targeting mutagenic pathways in an ancillary, “anti-evolution” strategy aimed at protecting existing and future TB drugs.